Engineering Setting on Traffic Lights Based on Number of Vehicles with Fuzzy Logic Algorithm - Iswanjono, Iswanjono; Putri, Regina Chelinia Erianda; Adiyanto, Ignasius Tegar (Sekolah Tinggi Teknologi Adisutjipto, 2018)
At crossroads there is often a queue of vehicles that are not evenly distributed in each branch, but the length of the green light remains (not adaptive). So prototype was made to regulate the green light based on the number of vehicles with the help of the Fuzzy Logic Algorithm. Beginning with the next fuzzification stage with the help of the rule base to the defuzzification stage which produces a long green light. The results of the study, Fuzzy Logic algorithm can set the length of green light for each branch based on the number of vehicles. If a branch has more vehicles than other branches, the length of time for the green light on the branch is longer than the other branches. The percentage of error testing with theoretical calculations is 0.05% and the percentage of success is 99.95%.